2007
DOI: 10.1099/vir.0.82510-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 94, a proposed new serotype in human enterovirus species D

Abstract: The genus Enterovirus (family Picornaviridae) contains five species with strains isolated from humans: Human enterovirus A (HEV-A), HEV-B, HEV-C, HEV-D and Poliovirus. In this study, a proposed new serotype of HEV-D was characterized. Four virus strains were isolated from sewage in Egypt and one strain from acute flaccid paralysis cases in the Democratic Republic of the Congo. The complete genome of one environmental isolate, the complete coding sequence of one clinical isolate and complete VP1 regions from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 53 publications
2
57
0
2
Order By: Relevance
“…In the species human enterovirus D (HEV-D), three serotypes, including EV68, EV70, and EV94 are known to causes illness in human (31,32). The VP1 sequences, the most variable genome region of enteroviruses, EV68 were shown to be closely related to those of EV70 and EV94 (26,32).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the species human enterovirus D (HEV-D), three serotypes, including EV68, EV70, and EV94 are known to causes illness in human (31,32). The VP1 sequences, the most variable genome region of enteroviruses, EV68 were shown to be closely related to those of EV70 and EV94 (26,32).…”
Section: Discussionmentioning
confidence: 93%
“…The VP1 sequences, the most variable genome region of enteroviruses, EV68 were shown to be closely related to those of EV70 and EV94 (26,32). It was previously reported that EV70 has affinity for ␣2-3 SAs (33).…”
Section: Discussionmentioning
confidence: 94%
“…EV70 was indeed first discovered in Ghana in 1969 during an acute hemorrhagic conjunctivitis epidemic (15) and has subsequently caused two global human pandemics with over 30 million cases reported worldwide (14), consistent with a sub-Saharan origin for this virus. A putative African origin for EV94 in species D was suggested by its initial detection in acute flaccid paralysis patients in the DRC and its recovery from wastewater in Egypt as part of a poliovirus surveillance program (12,34). Furthermore, neutralizing antibodies against EV70 have been detected in the sera of African cattle, sheep, swine, chickens, goats, and dogs (16), implying a much wider host range than typically found in other enterovirus species and consistent with in vitro observations of its ability, along with EV94 to replicate in the cells derived from a wide range of mammalian species (33,34,37).…”
Section: Discussionmentioning
confidence: 99%
“…A putative African origin for EV94 in species D was suggested by its initial detection in acute flaccid paralysis patients in the DRC and its recovery from wastewater in Egypt as part of a poliovirus surveillance program (12,34). Furthermore, neutralizing antibodies against EV70 have been detected in the sera of African cattle, sheep, swine, chickens, goats, and dogs (16), implying a much wider host range than typically found in other enterovirus species and consistent with in vitro observations of its ability, along with EV94 to replicate in the cells derived from a wide range of mammalian species (33,34,37). The finding of a further species D enterovirus in chimpanzees is thus entirely consistent with widespread circulation in a range of mammalian species in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination within the 5' UTR and the non-structural coding regions was also found among EV-A and EV-B members (within the same species) [129;134]. The frequency of recombination differs between EV species, being higher in EV-B species than in EV-A species [8] and very low in EV-D species [135,136].…”
Section: Recombination Of Enterovirusesmentioning
confidence: 99%